Produção e percepção das fricativas sibilantes em Porto Alegre/RS e Florianópolis/SC - Biasibetti, Ana Paula Correa da Silva (2018)
This thesis deals with the production and perception of voiceless sibilant fricatives [s] and [ʃ] in syllable onset and coda in the varieties of Brazilian Portuguese spoken in Porto Alegre/RS and Florianópolis/SC under the perspective of Sociophonetics (FOULKES, DOCHERTY, 2006; FOULKES; SCOBBIE; WATT, 2010; THOMAS, 2011). This research aims: i) to provide the acoustic description of the sibilant fricatives produced in Porto Alegre/RS and Florianópolis/SC in onset and coda; ii) to investigate the effects of the linguistic bias (contrastive and non-contrastive function of sibilant fricatives) on the phonetic perception of sibilant fricatives in onset and coda; and iii) to investigate the effects of the cognitive bias on the perception of phonetic variation of sibilant fricatives in coda. The corpus of this study consists of two samples of production data, one referring to data from 16 informants from Florianópolis and another sample referring to data from 24 informants from Porto Alegre. Regarding the perception data, the sample collected in Florianópolis consists of 30 participants, while the sample collected in Porto Alegre consists of 10 participants. The acoustic analysis of the sibilant fricatives partially confirmed the predicted coarticulatory effects of the surrounding vowel contexts and the effects of syllable stress on the spectral characterization of the sibilant fricatives, except for the vowels [u] and [o] preceding the fricative sibilant in coda and the unstressed pretonic syllable in the case of the alveolar fricative in onset. It seems that the variability of the phonetic production correlates with the gender of the speakers in the two cases indicated. The gender of the speakers also seems to interfere in the production of the alveolar fricative in onset by more educated people from Porto Alegre, with men tending to increase the Centroid, while women tend to reduce it. The temporal parameter examined showed a constant effect, namely the increase of frequencies as a function of the duration of the sibilants in onset and coda. The increase in frequencies due to the monitored speech style has also been confirmed and it is suggested to be an articulatory behavior associated specifically to women. Concerning the analysis of perception data, contrast and noncontrast relations of sibilant fricatives do affect the perception of men and women from Florianópolis and men from Porto Alegre, but not in the perception of women from Porto Alegre. Regarding the perception of phonetic variation, the results suggest that automatic associations between the stereotype of native/local resident and the palatoalveolar fricative in Florianópolis and the association between the stereotype of portoalegrense and the alveolar fricative in Porto Alegre are activated during perception. Moreover, the implicit association tends to become stronger as participants overtly report a greater difference between alveolar and palato-alveolar stimuli. However, the fact that some participants associate this difference to linguistic aspects other than the sibilant fricative in coda shows that the perception of socially structured phonetic variation occurs unconsciously. It is therefore concluded that the production of voiceless sibilant fricatives in Brazilian Portuguese is phonetically gradient and varies according to the gender of the speakers and that the perception of these sounds is mediated by linguistic and cognitive biases.